IMPLEMENTATION OF THE CONTINUING EDUCATION CONCEPT IN THE EUROPEAN EDUCATIONAL AREA: REGULATORY PROVISION - Svitlana Sysoieva; Olena Protsenko (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article reveals the European context of the meaning of the «continuing education» concept, which is interpreted in the Memorandum on Lifelong Learning as a purposeful educational activity conducted on an ongoing basis to improve the knowledge, skills and abilities of citizens and is a basic principle of the education system. Continuing education has become a key element in the European Union definition of strategies to build the world's most competitive and dynamic knowledge-based society. The analysis of international documents adopted by EU countries showed that the implementation of continuing education strategies in national systems is recognized as one of the priority areas and fundamental principles of educational system development in EU countries, which direct the national policy of their countries to implement the concept of lifelong learning and encourage higher education institutions increase access to education for different age groups. The system of continuing education is divided into three components. The first - additional professional education - contributes to the formation of the professional basis of human resources of the modern high-tech economy. The second component of the system of continuing education provides various groups with the opportunity to adapt to changing living conditions. The third component of the system of continuing education provides for the satisfaction of various individual educational needs of citizens. The implementation of the concept of continuing education is aimed at covering the educational programs of all people - from the youngest to the elderly. Attention is focused on finding ways to democratize access to education, increase the value of knowledge, increase investment in education and bring it closer to the consumer. The study and analysis of international documents on continuing education is necessary for the further development of the education system of Ukraine, which corresponds to the general trend of development of education systems in European and global space